Are Tattooing Indicators of Dark Personalities? An Analysis of Body Modification within the Framework of Dark Triad of Personality - Dan Florin Stanescu; Marius Constantin Romascanu (Journal of Social and Development Sciences, 2021)
There are several displays commonly labeled as body modifications, including body piercings, scarification, tattoos, cutting, etc. In this study, we were focused on one distinct form of body modification, namely tattoos. The current exploratory study investigated the connection between body modifications (BM) and Dark Triad personality for a sample of 77 university students with BM, compared to a control group of 77 non-BM individuals. Three self-administrated questionnaires were used to collect the data: Self-Report Psychopathy Scale-Short Form, Mach-IV scale, and Narcissistic Personality Inventory. The findings suggest that subclinical psychopathy is most strongly connected to body modifications. An increased number of tattoos was also significantly correlated with a higher level of anti-sociality. Participants with visible body modifications had significantly higher affective callousness and overall self-reported subclinical psychopathy levels, compared with individuals with non-visible alterations.